Identification of Initial Crack and Fracture Development Monitoring under Uniaxial Compression of Coal with High Bump Proneness. (21st December 2021) - Bi, Zuoqing; Liang, Han; Hui, Qianjia
Abstract : The rock burst proneness of coal is closely related to the coal mass structure. Therefore, the initial crack distribution of high burst proneness coal, its fracture development, and failure process under loading conditions are of great significance for the prediction of rock burst. In this study, high burst proneness coal is used to prepare experiment samples. The surface cracks of the samples are identified and recorded. The internal crack of the sample is detected by nuclear magnetic resonance (NMR) technology to determine the crack ratio of each sample. Then, 3D-CAD technology is used to restore the initial crack of the samples. Uniaxial compression test is carried out, and AE properties are recorded in the test. The stress-strain curve, the distribution of the fractural points within the sample at different stress states, and the relationship between ring count and stress are obtained. Results show that the stress-strain curves of high burst proneness coal are almost linear, to which the stress-ring count curves are similar. The distributions of fractural points in different bearing states show that the fracture points emerge in the later load stage and finally penetrate to form macrofracture, resulting in sample failure. This study reveals the initial crack distribution of coal with high burst proneness and the fracture development under bearing conditions, which provides a theoretical basis for the prediction technology of rock burst and technical support for the research of coal structure.